2016
DOI: 10.1002/14651858.cd011248.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding for procedural pain in infants beyond the neonatal period

Abstract: We conclude, based on the 10 studies included in this review, that breastfeeding may help reduce pain during vaccination for infants beyond the neonatal period. Breastfeeding consistently reduced behavioural responses of cry duration and composite pain scores during and following vaccinations. However, there was no evidence that breastfeeding had an effect on physiological responses. No studies included in this review involved populations of hospitalised infants undergoing other skin-breaking procedures. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 49 publications
0
60
0
9
Order By: Relevance
“…Nonpharmacologic methods that are commonly used to reduce the effects of invasive procedures in newborns include breastfeeding (Obeidat & Shuriquie, 2015;Pillai Ridell, et al, 2015;Harrison et al, 2016;Okan et al, 2010;Yilmaz & Arikan, 2011;Shah, Herbozo, Aliwalas, & Shah, 2012;Uga et al, 2008;Marín Gabriel et al, 2013;Aguilar Cordero, Mur Villar, García García, Rodríguez López, & Rizo Baeza, 2014), pacifiers (da Motta & da Cunha, 2015Yilmaz & Arikan, 2011), and sucrose and sweet solutions (Kassab, Anabrees, Harrison, Khriesat, & Chen, 2017;Kassab, Foster, Foureur, & Fowler, 2012;Pillai Riddell et al, 2015;Yilmaz & Arikan, 2011). Other alternatives include music therapy (Marofi, Nikobakht, Badiee, & Golchin, 2015); massage, touching, and positioning (Hartley, Miller, & Gephart, 2015); and nesting, kangaroo care, foetal positioning, and wrapping (Morrow et al, 2010;Prasopkittikun & Tilokskulchai, 2003;Okan et al, 2010;Obeidat & Shuriquie, 2015;Ali, McGrath, & Drendel, 2016;Cong, 2015;Shu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmacologic methods that are commonly used to reduce the effects of invasive procedures in newborns include breastfeeding (Obeidat & Shuriquie, 2015;Pillai Ridell, et al, 2015;Harrison et al, 2016;Okan et al, 2010;Yilmaz & Arikan, 2011;Shah, Herbozo, Aliwalas, & Shah, 2012;Uga et al, 2008;Marín Gabriel et al, 2013;Aguilar Cordero, Mur Villar, García García, Rodríguez López, & Rizo Baeza, 2014), pacifiers (da Motta & da Cunha, 2015Yilmaz & Arikan, 2011), and sucrose and sweet solutions (Kassab, Anabrees, Harrison, Khriesat, & Chen, 2017;Kassab, Foster, Foureur, & Fowler, 2012;Pillai Riddell et al, 2015;Yilmaz & Arikan, 2011). Other alternatives include music therapy (Marofi, Nikobakht, Badiee, & Golchin, 2015); massage, touching, and positioning (Hartley, Miller, & Gephart, 2015); and nesting, kangaroo care, foetal positioning, and wrapping (Morrow et al, 2010;Prasopkittikun & Tilokskulchai, 2003;Okan et al, 2010;Obeidat & Shuriquie, 2015;Ali, McGrath, & Drendel, 2016;Cong, 2015;Shu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…After participating in this study, the majority of mothers reported the intention to use breastfeeding, SSC, or sweet‐tasting solutions in future painful procedures performed in their infants, such as vaccination and blood collection. It is worth highlighting that the analgesic effects of breastfeeding 42 and sweet‐tasting solutions 43 persist up to one year old, which indicates that the video may impact pain management practices beyond hospital discharge. Further studies are recommended to ascertain effectiveness of the video in improving pain management during early childhood vaccinations and other painful procedures.…”
Section: Discussionmentioning
confidence: 99%
“…N. Witt и соавт. (2016) предлагают рассмотреть многоуровневый подход к контролю процедурной боли [11][12][13].…”
Section: фармакологические вмешательстваunclassified